The Effect of the Implementation of Dictogloss Technique on Listening Comprehension of the 10th Grade Students Of SMA Negeri 1 Sukasada - I. K. A. H. Yasa Dinatha (Journal of Psychology and Instruction, 2017)
This study aimed at investigating whether or not there was a significant effect of the implementation of Dictogloss technique upon listening comprehension of the tenth grade students of SMA Negeri 1 Sukasada. The research was an experimental one with Post-test Only Control Group Design. The population was the tenth grade students of SMA Negeri 1 Sukasada. Cluster Random Sampling was assigned to select the sample of the study. The samples were 20 students at grade X3 for experimental group and 21 at grade X2 for control group. The experimental group was taught by using Dictogloss technique and the control group was taught by using conventional teaching technique. The data was analyzed by using T-test through SPSS program. The result of the data analysis showed that students in experimental group performed better than the students in control group. It was proven by the result of the descriptive statistics that showed the mean score of the experimental group was 81.40 while the mean score of the control group was 78.24. The result of the t-test also showed that the value of the tobs was higher than the tcv. The value of the tobs was 2.185 while the value of the tcv was 2.023. It can be concluded that there was a significant effect on students’ listening achievement that were taught by using Dictogloss technique than were taught by using conventional teaching technique.